DuckDB in action - Needham, Mark; Hunger, Michael; Simons, Michael (Manning Publications, 2024)
DuckDB in Action guides you example-by-example from setup, through your first SQL query, to advanced topics like building data pipelines and embedding DuckDB as a local data store for a Streamlit web app. You'll explore DuckDB's handy SQL extensions, get to grips with aggregation, analysis, and data without persistence, and use Python to customize DuckDB. A hands-on project accompanies each new topic, so you can see DuckDB in action.
Includes bibliographical references and index
Keywords: Database management -- Computer programs; DuckDB (Computer programs); Open source software; Bases de données; Gestion; Logiciels; Logiciels libres